A Tin Box (diségno, 2020)
Could it have been the remoteness in which I now find myself, or the peculiarity of this house, of this road, ofthe name of this road, to impose on me these nocturnal wanderings of the mind which, for some time now, I havebecome used to living with?Who or what is the true author of this writing, I will not be able to determine, and if at the beginning I could stillventure the illusion of autonomous choices, it has been enough, after having gone through a few dozen pages, forme to realize that, slowly or in a rapid hurry, I can no longer guarantee to maintain a firm control of the contents.As to the late professor of latinitas, inhabitant of the floors of this house, which now I, in his place, am treading,I would never have imagined him capable of opening up to me such a necessary perlustration into the protagonists and the anxieties of my life. (read more)